Synergistic effect of fruit-vegetable powder and Staphylococcus on the physicochemical properties and microbial community of Yunnan dry-cured beef - Jiayan Tan; Qiongfang Yang; Guozhou Liao; Shuai Tang; Ruwei Ren; Yanfei Du; Jia Liu; Nannan Zhou; Wen Xun; Guiying Wang (International Journal of Gastronomy and Food Science, 2026)

TMT-based quantitative proteomics analysis reveals the synergistic effect of vegetable powder and Staphylococcus on the quality characteristics of Yunnan dry-cured beef - Ruwei Ren; Shuai Tang; Guiying Wang; Jia Liu; Nannan Zhou; Wen Xun; Yanfei Du; Jiayan Tan; Guozhou Liao (Food Bioscience, 2025)

Smartphone-assisted portable electrochemical sensing platform for point-of-care detection of thiocyanate using a laser-induced graphene composite electrode - Xiaoming Yuan; Linlin Chen; Ruwei Liu; Shilin Li; Xiu-wen Wu; Yunhan Ling (Analytica Chimica Acta, 2025)

Motor-Cognitive Dual-Task Cost and Associated Micro Lesions of Cerebellum and Brainstem in Multiple System Atrophy (Parkinsonian Type) - Yi Xiao; Shichan Wang; Yanbing Hou; Junyu Lin; Tianmi Yang; Qirui Jiang; Jiyong Liu; Ruwei Ou; Chunyu Li; Huifang Shang (The Cerebellum, 2025)

Ornithogenic sedimentary profiles of n-alkanes and PAHs constrain breeding penguin population dynamics at Cape Bird, Ross Island, Antarctica, over the past 1,500 years - Zhixiang Liu; Yaguang Nie; Ruwei Wang; Qing Huang; Hong Yan; Ming Hung Wong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Optimizing the development of contaminated land in China: Exploring machine-learning to identify risk markers - Xiufeng Ni; Zeyuan Liu; Jizhong Wang; Mengting Dong; Ruwei Wang; Zhulin Qi; Haolong Xu; Chao Jiang; Qingyu Zhang; Jinnan Wang (Journal of Hazardous Materials, 2024)

The genome-wide characterization and associated cold-tolerance function of the superoxide dismutase in the cold response of the tick Haemaphysalis longicornis - Zhijun Yu; Ruotong Wang; Tianai Zhang; Tongxuan Wang; Chuks F. Nwanade; Tingwei Pei; Ruwei Bai; Zihao Wang; Jingze Liu (Pesticide Biochemistry and Physiology, 2023)

Distributed acoustic sensing for shallow structure imaging using mechanical noise: A case study in Guangzhou, China - Wenbin Jiang; Jiangnan Lin; Bin Liu; Ruwei Zhang; Baojin Zhang; Zhen Yang; Yuan Gu (Journal of Applied Geophysics, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Geochemistry of uranium in Chinese coals and the emission inventory of coal-fired power plants in China - Jian Chen; Ping Chen; Duoxi Yao; Wenhui Huang; Shuheng Tang; Kejian Wang; Wenzhong Liu; Youbiao Hu; Qingguang Li; Ruwei Wang (International Geology Review, 2018)

Particle-Associated Polycyclic Aromatic Hydrocarbons (PAHs) in the Atmosphere of Hefei, China: Levels, Characterizations and Health Risks - Ruoyu Hu; Guijian Liu; Hong Zhang; Huaqin Xue; Xin Wang; Ruwei Wang (Archives of Environmental Contamination and Toxicology, 2018)

Characteristic and Source of Atmospheric PM10- and PM2.5-bound PAHs in a Typical Metallurgic City Near Yangtze River in China - Hong Zhang; Ruwei Wang; Huaqin Xue; Ruoyu Hu; Guijian Liu (Bulletin of Environmental Contamination and Toxicology, 2018)

Bioavailability evaluation, uptake of heavy metals and potential health risks via dietary exposure in urban-industrial areas - Balal Yousaf; Guijian Liu; Ruwei Wang; Muhammad Imtiaz; Muhammad Zia-ur-Rehman; Mehr Ahmed Mujtaba Munir; Zhiyuan Niu (Environmental Science and Pollution Research, 2016)

Bisphenol A exposure and healing effects of Adiantum capillus-veneris L. plant extract (APE) in bisphenol A-induced reproductive toxicity in albino rats - Balal Yousaf; Amina; Guijian Liu; Ruwei Wang; Abdul Qadir; Muhammad Ubaid Ali; Qudsia Kanwal; Bushra Munir; Asmatullah; Zaigham Abbas (Environmental Science and Pollution Research, 2016)

Levels and distributions of polycyclic aromatic hydrocarbons (PAHs) in middle reach of Huaihe River, China: anthropogenic influences and ecological risks - Jiamei Zhang; Guijian Liu; Zijiao Yuan; Ruwei Wang (Natural Hazards, 2014)

Levels and Patterns of Polycyclic Aromatic Hydrocarbons in Coal-Fired Power Plant Bottom Ash and Fly Ash from Huainan, China - Wang Ruwei; Zhang Jiamei; Liu Jingjing; Guijian Liu (Archives of Environmental Contamination and Toxicology, 2013)

Environmental Assessment of PAHs in Soils Around the Anhui Coal District, China - Ruwei Wang; Guijian Liu; Chen-Lin Chou; Jingjing Liu; Jiamei Zhang (Archives of Environmental Contamination and Toxicology, 2010)